Analysis of regional innovation mapping in order to encourage strategic public policies in North Kalimantan Province - Arif Arianto; Dian Suryanata; Mustakim Mustakim (International Journal of Regional Innovation, 2022)
This research is about mapping the Regional Innovation of North Kalimantan Province. The focus of this research is the mapping of regional innovations proposed by Regional Apparatus Organizations as an effort to support the effectiveness and efficiency of implementing OPD tasks related to governance, public services and regional competitiveness. This research is important to do because this study will discuss efforts to map regional innovations, especially in North Kalimantan Province in order to realize accelerated economic growth, regional competitiveness and improve people's welfare in North Kalimantan Province. The population in this study are regions that have implemented regional innovations. While the subject in this study is the regional innovation of North Kalimantan Province. The results of the study show that the Innovation of North Kalimantan Province is spread over 25 affairs out of 32 affairs that are under regional authority. When viewed from regional government affairs, the three regional innovations with the function of supporting affairs became the most innovations, namely 13 innovations, from health there were 9 innovations, and from community empowerment 9 innovations became the innovations with the highest number. Meanwhile, the innovations with the fewest issues are those from education, social, library, energy, forestry and youth affairs. and from community empowerment as many as 9 innovations to innovations with the largest number. Meanwhile, the innovations with the fewest issues are those from education, social, library, energy, forestry and youth affairs. and from community empowerment as many as 9 innovations to innovations with the largest number. Meanwhile, the innovations with the fewest issues are those from education, social, library, energy, forestry and youth affairs.